Hidden champions - how young and small technology-oriented firms can attain high export-sales ratios - Helmut Fryges (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Determinants of a firm?s export-sales ratio (degree of internationalisation) are frequently discussed in the literature related to individual firms? export activities. Stylised facts show a positive relationship between firm size and firm age on the one hand and the firm?s export-sales ratio on the other hand. However, anecdotic evidence and recent empirical results revealed that it is not size or age per se that leads to a high export-sales ratio. This paper analyses the export-sales ratio of a sample of young technology-oriented firms in Germany and the UK. The empirical results confirm that neither youth nor smallness are necessarily an obstacle to realising a high degree of internationalisation. However, this requires that the firms possess firm-specific assets in order to overcome barriers to entry into the foreign market. These firm-specific assets may be acquired via conducting own R&D activities, buying novel technology from other companies, or by employing internationally experienced managers.
Keywords: L60; F23; L86; 330; High-technology industries; export-sales ratio; fractional logit model